Taurine regulates insulin release from pancreatic beta cell lines - L’Amoreaux, William J (BioMed Central, 2010)
BACKGROUND: Pancreatic β-cells release insulin via an electrogenic response triggered by an increase in plasma glucose concentrations. The critical plasma glucose concentration has been determined to be ~3 mM, at which time both insulin and GABA are released from pancreatic β-cells. Taurine, a β-sulfonic acid, may be transported into cells to balance osmotic pressure. The taurine transporter (TauT) has been described in pancreatic tissue, but the function of taurine in insulin release has not been established. Uptake of taurine by pancreatic β-cells may alter membrane potential and have an effect on ion currents. If taurine uptake does alter β-cell current, it might have an effect on exocytosis of cytoplasmic vesicle. We wished to test the effect of taurine on regulating release of insulin from the pancreatic β-cell. METHODS: Pancreatic β-cell lines Hit-TI5 (Syrian hamster) and Rin-m (rat insulinoma) were used in these studies. Cells were grown to an 80% confluence on uncoated cover glass in RPMI media containing 10% fetal horse serum. The cells were then adapted to a serum-free, glucose free environment for 24 hours. At that time, the cells were treated with either 1 mM glucose, 1 mM taurine, 1 mM glucose + 1 mM taurine, 3 mM glucose, or 3 mM glucose + 1 mM taurine. The cells were examined by confocal microscopy for cytoplasmic levels of insulin. RESULTS: In both cell lines, 1 mM glucose had no effect on insulin levels and served as a control. Cells starved of glucose had a significant reduction (p<0.001) in the level of insulin, but this level was significantly higher than all other treatments. As expected, the 3 mM glucose treatment resulted in a statistically lower (p<0.001) insulin level than control cells. Interestingly, 1 mM taurine also resulted in a statistically lower level of insulin (p<0.001) compared to controls when either no glucose or 1 mM glucose was present. Cells treated with 1 mM taurine plus 3 mM glucose showed a level of insulin similar to that of 3 mM glucose alone. CONCLUSIONS: Taurine administration can alter the electrogenic response in β-cell lines, leading to a change in calcium homeostasis and a subsequent decrease in intracellular insulin levels. The consequence of these actions could represent a method of increasing plasma insulin levels leading to a decrease in plasma glucose levels.